Urban economics and fiscal policy - Sieg, Holger (Princeton Princeton University Press, 2020)
With more than half of today$1 (Bs global GDP being produced by approximately four hundred metropolitan centers, learning about the economics of cities is vital to understanding economic prosperity. This textbook introduces graduate and upper-division undergraduate students to the field of urban economics and fiscal policy, relying on a modern approach that integrates theoretical and empirical analysis. Based on material that Holger Sieg has taught at the University of Pennsylvania, Urban Economics and Fiscal Policy brings the most recent insights from the field into the classroom.s